The discovery of microbial consortium from tiger milk mushroom culture environment - Ho, Chen Ee (2025)
The tiger milk mushroom (Lignosus rhinocerotis), a vital medicinal fungus native to tropical regions. The objectives of this study were established to identify the microbial consortium present in the culture environment of L. rhinocerotis and discuss the discovered functional contributions of these microbes to the fungus. There has been little research on microbial consortia in tiger milk mushroom cultures, and the active chemicals responsible for their medicinal benefits have yet to be found. Despite research into its bioactivity, no chemicals from L. rhinocerotis have been identified. Understanding the symbiotic connections among these consortia is critical for optimising growing practices and increasing mushroom production and nutraceutical value. The objective goals were achieved by obtaining pure cultures from both the outer layer of the sclerotium, containing soil samples, and the inner core. Two cultures were isolated, labeled, and subjected to amplicon sequencing for identity verification using the UNITEv10 database. The culture from the outer layer was identified as Talaromyces viridulus (97.546% ID, 71% coverage, accession number JN899314), while the inner core culture was recognized as Talaromyces assiutensis (99.413% ID, 44% coverage, accession number MH861122). The presence of Talaromyces species in L. rhinocerotis cultures suggests remarkable possibilities for their connection and potential interactions. Referring Talaromyces assiutensis' antioxidant, antibacterial, and anticancer characteristics, it is possible that Talaromyces species coexist with L. rhinocerotis and contribute to its therapeutic benefits. More study is needed to understand the nature of this interaction and its significance in increasing the therapeutic characteristics of L. rhinocerotis.